Aqidah Akhlak Teacher's Strategy In Overcoming The Negative Impact Of The Tiktok Application (Case study of the negative impact of TikTok on Mts Darun Najah Sumber Anyar students in 2023) - Fathorrahman; Ahmad Maddah Hamdani (Penerbit Hellow Pustaka, 2024)
TikTok is one of the social media platforms that has gained popularity among a wide range of people, from teenagers to adults. Its attractiveness lies in offering a plethora of current and engaging video content that captures everyone's attention. However, behind its captivating content, the TikTok application harbors many potential negative impacts, such as consuming a considerable amount of time for its users, creating addiction, and the abundance of adult content, which can undoubtedly affect its users, including students. Therefore, teachers, particularly those instructing in Aqidah Akhlak (Islamic ethics and morality), play a crucial role in preventing moral crises due to the negative effects of TikTok. This research employs a qualitative case study approach, with data sources obtained from Aqidah Akhlak instructors, guidance and counseling teachers, and students. The data collection methods include observation, interviews, and documentation. Data analysis is carried out by reducing data, presenting data, and drawing conclusions. The technique used to check the validity of the data is triangulation. The results of this study reveal the strategies employed by Aqidah Akhlak teachers in addressing the negative impact of the TikTok application. These strategies involve preventive measures, including providing guidance on the negative effects of the TikTok application and setting a positive example for students. Additionally, Aqidah Akhlak instructors organize congregational Dhuhr prayers and encourage the memorization of short verses from the Quran during free time. Sanctions are also applied by Aqidah Akhlak instructors if a student persists in disregarding warnings. The implementation of these strategies has a positive impact on the way students speak and behave, making them more adept at navigating social media, especially the TikTok application.